ANALISIS FAKTOR YANG MEMPENGARUHI PARTISIPASI PESERTA DIDIK DALAM PEMBELAJARAN AKUNTANSI - Dewi, Maria Yusmila; Ulfah, Maria; Matsum, Junaidi H (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research was to knowthe factors of influence of the students in class XI AK 1 at SMK Kristen Immanuel II Pontianak. The background og this research was a finding of problom when the reseacher did the observation about student participation in learning accounting. The method of this research was student of class XI accounting skills program, amounting to 42 students and teachers of accounting subject. Data collection was obtained through observation and interview guidliness. The analized using data reduction, data presentation and verification/drawing conclusion of student participation based on comparison of number (percentager) a predicater, then checking the validity of the data using triangulation technique. The observation was conducted twice and interview as much as two days. The result showed that human factor including personality and classmates that affect students participation can be said to be low, while environmental factors that include facilities and sitting position of student that affect student participation can be said to be high.Keyword : Participation, Factor of human, Factor of environmental